2013
DOI: 10.1039/c3dt50664a
|View full text |Cite
|
Sign up to set email alerts
|

A chiral mixed metal–organic framework based on a Ni(saldpen) metalloligand: synthesis, characterization and catalytic performances

Abstract: A three-dimensional (3D) chiral mixed metal-organic framework [Cd4Cl(Ni-L)3(Ni-HL)(H2O)6(DMF)]·4DMF (CMOF 1) based on a new enantiopure dicarboxyl-functionalized Ni(saldpen) metalloligand Ni-H2L and a novel tetranuclear cadmium cluster [Cd4Cl(CO2)7(CO2H)] has been synthesized and characterized by elemental analyses, IR and UV-vis spectra, thermogravimetric analysis, nitrogen and carbon dioxide adsorption, powder and single-crystal X-ray diffractions. Each tetranuclear-cadmium cluster in 1 is linked by eight Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 83 publications
0
38
0
Order By: Relevance
“…The best result was obtained using a combination of (R)-(+)-binaphthol in conjunction A novel three-dimensional chiral mixed metal-organic framework (MOF) based on an enantiopure nickel(II)(salen) metalloligand and a tetranuclear cadmium cluster was reported by Jiang and co-workers in 2013 [29]. With each cadmium cluster linked by eight nickel complexes and each nickel complex surrounded by two cadmium clusters, a three-dimensional structure which displayed both high porosity and stability was generated.…”
Section: Other Metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The best result was obtained using a combination of (R)-(+)-binaphthol in conjunction A novel three-dimensional chiral mixed metal-organic framework (MOF) based on an enantiopure nickel(II)(salen) metalloligand and a tetranuclear cadmium cluster was reported by Jiang and co-workers in 2013 [29]. With each cadmium cluster linked by eight nickel complexes and each nickel complex surrounded by two cadmium clusters, a three-dimensional structure which displayed both high porosity and stability was generated.…”
Section: Other Metal Complexesmentioning
confidence: 99%
“…This showed that chloride or tosylate counterions on the chromium centre gave enantioselective catalysts though with low s values (1.1-2.2). Subsequently, the effect of the co-catalyst was studied and the results showed that a combination of chromium(III)(salen) acetate and PPNCl [(bis-(triphenylphosphoranylidene)ammonium chloride)] was the most efficient catalyst for the kinetic resolution of phenyl glycidyl ether 1c, achieving 84% conversion and a s value of 3.1 at 25 °C and one atmosphere of carbon dioxide pressure for 24 h. Similarly, the use of N-(2,3-epoxypropyl)diphenylamine 1b gave a s value of 7.3 when the reaction was carried out at 25 °C and one atmosphere of carbon dioxide pressure for 3 h. A novel three-dimensional chiral mixed metal-organic framework (MOF) based on an enantiopure nickel(II)(salen) metalloligand and a tetranuclear cadmium cluster was reported by Jiang and co-workers in 2013 [29]. With each cadmium cluster linked by eight nickel complexes and each nickel complex surrounded by two cadmium clusters, a three-dimensional structure which displayed both high porosity and stability was generated.…”
Section: Other Metal Salen Complexesmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) have attracted tremendous interests and an enormous amount of MOFs have been designed and synthesized for energy‐, environment‐ and medicine‐relevant applications, such as gas sorption, luminescence, sensors and so on. Especially, MOFs used as heterogeneous catalysts have been developed dramatically during the past decade and many MOF‐based catalysts containing various types of catalytic sites have been reported . Among them, the most intensively investigated topic is MOF‐based Lewis acid catalysts that utilize the coordinatively unsaturated metal centers in MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…However, these MOF catalysts often suffer from the possible collapse of frameworks after catalytic reaction since the coordinatively unsaturated metal centers are also responsible for the stability of the frameworks. To overcome this problem, a more rational strategy is to utilize metalloligands involving well‐defined catalytic sites rather than pure organic ligands to construct MOF catalysts . For example, we have reported two Ni(salen)‐based MOFs that could be used as efficient and recyclable heterogeneous catalysts for the synthesis of cyclic carbonates by the cycloaddition of CO 2 with epoxides using the Ni(salen) moieties as Lewis acid catalytic sites .…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) have seen a huge increase in interest in recent years, due to their potential as porous materials for a wide variety of applications, such as gas sorption and storage, 1-5 catalysis [6][7] and in separations. [8][9][10] Reasons MOFs are so attractive for such a wide variety of applications include their crystalline nature, their high porosity and their potential for controlled modifications of their structures and pore surfaces.…”
Section: Introductionmentioning
confidence: 99%